ANALYSIS OF FIRE POST PLACEMENT BASED ON FIRE RISK IN KATINGAN HILIR DISTRICT, KATINGAN REGENCY - Yoshua Paskaputra; Theresia Susi; Singgih Hartanto; Tari Budayanti Usop; Herwin Sutrisno; Petrisly Perkasa (RADJA PUBLIKA, 2025)
This study aims to analyze fire vulnerability levels and determine the optimal placement of fire stations in Katingan Hilir District, Katingan Regency, Central Kalimantan. Using a quantitative method and spatial modeling approach, the research integrates ten years of NASA MODIS satellite data (2015–2024) focusing on three key variables: fire hotspots, rainfall, and land cover. Findings reveal that 48.5% of the 301 recorded fire hotspots were not covered by the three existing fire stations, with the highest concentration found in Hampangen Village. Based on spatial overlay modeling and a 15-minute response time standard, the study recommends establishing a new fire station in this high-risk area. This spatial assessment offers valuable input for adaptive spatial planning and aims to enhance the regional fire risk management system.